2019
DOI: 10.5603/gp.2019.0101
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of spectral Doppler parameters in uterine arteries of patients with locally advanced squamous cell cervical cancer

Abstract: Objectives: Evaluate spectral Doppler parameters peak systolic velocity (PSV), end diastolic velocity (EDV), resistance index (RI) and pulsatility index (PI) in infiltrated and non-infiltrated uterine arteries of patients with locally advanced (stages II B, III B) squamous cell cervical cancer and their changes during treatment.Material and methods: the study group included 36 patients aged 35-78 years old. At diagnosis, PSV, EDV, RI and PI in uterine arteries were examined and compared with MRI findings. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Colposcopy is an imaging means currently used to screen for precancerous cervical lesions, which can amplify the image of the cervix and vagina mucosa, enable more precise visualization of tiny lesions, vascular tissue, and suspicious areas on the surface of the cervix that are not visible to the naked eye, and localize the biopsy to improve test accuracy. erefore, combining colposcopy with serum detection can eliminate problems such as unnecessary treatment for false positive patients and ensure safety, reliability, and strong operability, which is suitable for clinical diagnosis and efficacy determination [24]. In this study, the efficacy of Fuzheng Peiyuan decoction in the treatment of moderate to advanced cervical cancer was evaluated by the combined test, and by plotting the ROC curve, it was found that combined test had an area under the curve larger than each single test, and high sensitivity, and specificity, and therefore it might serve as an effective diagnostic modality to objectively evaluate the treatment effect of cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Colposcopy is an imaging means currently used to screen for precancerous cervical lesions, which can amplify the image of the cervix and vagina mucosa, enable more precise visualization of tiny lesions, vascular tissue, and suspicious areas on the surface of the cervix that are not visible to the naked eye, and localize the biopsy to improve test accuracy. erefore, combining colposcopy with serum detection can eliminate problems such as unnecessary treatment for false positive patients and ensure safety, reliability, and strong operability, which is suitable for clinical diagnosis and efficacy determination [24]. In this study, the efficacy of Fuzheng Peiyuan decoction in the treatment of moderate to advanced cervical cancer was evaluated by the combined test, and by plotting the ROC curve, it was found that combined test had an area under the curve larger than each single test, and high sensitivity, and specificity, and therefore it might serve as an effective diagnostic modality to objectively evaluate the treatment effect of cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that persistent HPV infection is a major causative factor in cervical cancer, but only a small proportion of patients with HPV infection will eventually progress to cervical cancer. In cervical cancer patients, the mode of treatment depends on staging and parametrial infiltration, which is a critical factor in determining treatment planning [10]. Etiological studies have shown that the occurrence of this cancer is a complicated process that includes many factors, and its molecular mechanism has not yet been fully explained.…”
Section: Introductionmentioning
confidence: 99%